1988
DOI: 10.1161/01.cir.78.4.1047
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ischemia on calcium-dependent fluorescence transients in rabbit hearts containing indo 1. Correlation with monophasic action potentials and contraction.

Abstract: The effects of acute global ischemia on cytosolic calcium transients were studied in perfused rabbit hearts loaded with the fluorescent calcium indicator indo 1. Indo 1-loaded hearts were illuminated at 360 nm, and fluorescence was recorded simultaneously at 400 and 550 nm from the epicardial surface of the left ventricle. The F4m/F550 ratio was calculated by an analog circuit, which allowed cancellation of optical motion artifact. Resulting calcium transients demonstrated a rapid upstroke and slow decay simil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
114
1

Year Published

1992
1992
2008
2008

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 257 publications
(132 citation statements)
references
References 43 publications
17
114
1
Order By: Relevance
“…31 The alternans in the calciumdependent fluorescence transient was also reported in ischemic rabbit hearts. 32 In this study, however, treatment with verapamil did not suppress the ST a . This suggested that the other mechanism may work on the flecainide-induced ST a .…”
Section: Mechanism Of St a Due To Flecainidecontrasting
confidence: 65%
“…31 The alternans in the calciumdependent fluorescence transient was also reported in ischemic rabbit hearts. 32 In this study, however, treatment with verapamil did not suppress the ST a . This suggested that the other mechanism may work on the flecainide-induced ST a .…”
Section: Mechanism Of St a Due To Flecainidecontrasting
confidence: 65%
“…Although the mechanism underlying alternans is not completely understood, alternations in contractile force are thought to result from variations in intracellular calcium release. 8 Additional evidence of impaired SR function at increasing stimulation rates with heart failure reported by other investigators 1 ' 2 ' 6 are fusion of Ught transients and contraction with increases in both enddiastolic intracellular calcium concentration and end-diastolic tone and a decrease in peak active tension development. Under the same conditions, control muscle preparations did not exhibit fusion or a decline in the force of contraction.…”
Section: -32mentioning
confidence: 76%
“…There are several reports of electrical-mechanical discordance under disease conditions. For example, Lee et al (1988) have shown electrical-mechanical discordance (short APD associated with large calcium transient) in ischemic hearts. Murphy et al (1994) have also shown electrical-mechanical discordant alternans, but in normal Landrace pigs that were paced rapidly.…”
Section: Voltage and Calcium Couplingmentioning
confidence: 99%